Development of E-LKPD VAK Using Liveworksheets in Science Learning in Grade IV of SDN 25 Pulau Punjung: Pengembangan E-LKPD VAK Menggunakan Liveworksheet pada pembelajaran IPAS di kelas IV SDN 25 Pulau Punjung - Ahmad Ilham Asmaryadi; Wiwik Okta Susilawati; Navinga Revi Yanti (Journal of Vocational Education and Information Technology (JVEIT), 2026)
This study was conducted because science and social science learning was still dominated by the use of textbooks and printed worksheets, which had not optimally accommodated students' diverse learning styles. The study aimed to develop a **Visual, Auditory, and Kinesthetic (VAK)-based Electronic Student Worksheet (E-LKPD)** using Liveworksheets for Science and Social Studies (IPAS) learning in Grade IV at SDN 25 Pulau Punjung. This research employed a Research and Development (R&D) approach using the Four-D model, consisting of the define, design, develop, and disseminate stages. The quality of the product was evaluated through validity, practicality, and effectiveness tests. The results showed that the E-LKPD achieved a content validity score of 92.8% (very valid), a language validity score of 77.5% (valid), and a graphical feasibility score of 97.5% (very valid). The practicality test indicated a teacher response score of 78.5% (practical) and a student response score of 93.2% (very practical). The effectiveness test demonstrated that the implementation of the E-LKPD resulted in a 100% learning mastery rate in both the trial class and the implementation class at another school, indicating that the product was highly effective. Therefore, the VAK-based E-LKPD developed using Liveworksheets is feasible to be used as a digital teaching material to support Science and Social Studies (IPAS) learning in elementary schools.